EKSPERIMENTASI MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEADS TOGETHER DAN THINK PAIR SHARE DENGAN QUANTUM LEARNING DITINJAU DARI KECERDASAN MATEMATIS LOGIS SISWA SMP SE-KABUPATEN MAGELANG TAHUN PELAJARAN 2014/2015 - Tanti Listiani; Tri Atmojo Kusmayadi; Riyadi Riyadi (Jurnal Pembelajaran Matematika, 2016)
Abstract: The purpose of this study was to determine the effect of learning models on learning achievement viewed from the logical mathematical intelligence of the students. The learning models compared were the cooperative learning model of the Numbered Heads Together (NHT) type modified with Quantum Learning and scientific approach, Think Pair Share (TPS) type with Quantum Learning and scientific approach, and classical model with scientific approach. The type of this study was a quasi-experimental research with a 3×3 factorial design. The population was all of students on grade VIII of Junior High Schools in Magelang Regency in academic year 2014/2015. The data was analyzed by using two way analysis of variance with unbalanced cells. Based on the hypothesis, the results of the study could be summarized as follows. (1) NHT-Quantum Learning gave better achievement than TPS-Quantum Learning and classical model, TPS-Quantum Learning had same achievement as classical model. (2) Students with high logical mathematical intelligence gave better achievement than middle and low logical mathematical intelligence, students who had middle logical mathematical intelligence gave better achievement than those who had low logical mathematical intelligence. (3) In each category of the logical mathematical intelligence, NHT-Quantum Learning gave better achievement than TPS-Quantum Learning and classical model, TPS-Quantum Learning had same achievement as classical model. (4) In each of the learning models, the students who had high logical mathematical intelligence got better achievement than middle and low logical mathematical intelligence, the students who had middle logical mathematical intelligence got better achievement than those who had low logical mathematical intelligence.Keywords: Numbered Heads Together, Think Pair Share, Classical, Quantum Learning, Logical Mathematical Intelligence.